CONFLICT DYNAMIC FRAMEWORK: RELIGIOUS CONFLICT ISSUES IN SPECIAL REGION OF YOGYAKARTA - Nababan, Kristina Roseven (Bina Nusantara University, 2019)
The researcher analyzed the conflict dynamic framework of religious conflict issues in the Special Region of Yogyakarta in 2014-2017. The research used qualitative descriptive research. Data collection techniques were primary data through interviews, observations, and secondary data through literature studies. Data analysis included data reduction, presentation, and verification. The results show that the conflict escalation degree in these past three years commonly is at the mass mobilization. Public-influencing religious and social figures successfully de-escalate it. Moreover, structural factors are triggered by education and policy of house of worship building, religious preaching, and exclusiveness. Those are also accelerated by society?s aggressiveness. Actors of conflict, in this case, are probably mass organizations and migrant communities. The related government agencies to resolve the conflict, and active participation from religious leaders, public figures, police, military, Ministry of Religious Affairs, Ministry of Law and Human Rights, Komisi Pemilihan Umum (KPU - General Elections Commission of Indonesia), and Badan Pengawas Pemilihan Umum (Bawaslu - Election Supervisory Board of Indonesia) are proven to have capacity to settle the issue.